West African Spatial Patterns of Economic Activities: Combining the ‘Spatial Factor’ and ‘Mobile Space’ Approaches - (:unkn) unknown (My University, 2015)
Over the last 30 years, two different bodies of literature developed by both U.S. historians and francophone geographers have moved toward similar conclusions regarding West African economic spatial patterns. Despite their different backgrounds, both the " spatial factor " approach promoted by historians and the " mobile space " approach developed by geographers view exchange centers as nodes of transnational trade networks and places in production territories, and perceive spatial dynamics as highly dependent on shifts of trade flows and production activities. The objective of this paper is to bring these two approaches together. We analyze the linguistic, disciplinary and geographic barriers that have separated them, and explain why and how these obstacles are being overcome. We then turn to what the two approaches have in common, notably their emphasis on actors in space, particularly traders, and where their differences lie. Finally, we show how a combined approach can make a significant contribution to the scholarly study of space in West Africa. We argue that continuing dialogue among fields can contribute to a reassessment of development policies.
Keywords: African Research